Definisi dan landasan dasar pendidikan islam - Fu'adi, Eka Agustin (Maliki Interdisciplinary Journal, 2025)
Islamic education plays a crucial role in shaping an individual's attitudes, morals, and character in accordance with the principles of Islamic teachings. This study aims to explore the concept of Islamic education and the foundational principles that support it. The research method employed is a literature review with a descriptive-analytical approach. The findings indicate that Islamic education is not solely focused on imparting knowledge but also strives to cultivate a personality that embodies noble character and behavior in line with religious values. The Qur'an and Hadith are the primary sources of Islamic education, with the main goals including character development, strengthening spiritual values, and enhancing intellectual capacity.